Optimization of bulblet production by leaf cuttings in Lachenalia - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2013)
Dissertation (M Inst Agrar ( Horticulture Science))--University of Pretoria, 2006.